Моделирование процесса олигомеризации фракции С9 жидких продуктов пиролиза - Бондалетов В. Г. Владимир Григорьевич; Ляпков А. А. Алексей Алексеевич; Мельник Е. И. Елена Ивановна; Огородников В. Д. (2013, 2013)
Заглавие с экрана